Effect Of Reward, Work Environment And Mutations On Performance Of Employees Pt. Services Raharja Surabaya - Rina Indra Sabella (Jurnal Mantik, 2022)
The purpose of this study was to determine the effect of rewards, work environment, and mutations on employee performance at PT. Jasa Raharja Surabaya. There are several factors that cause high or low employee performance, in this study the company needs to provide feedback that will have an impact on company performance. Factors that affect employee performance in this study are rewards, work environment, and mutations. The data used in this study are primary data obtained from distributing questionnaires. The sample was selected as many as 72 people with random sampling technique on employees of PT. Jasa Raharja Surabaya. Statistical analysis used is multiple linear regression analysis.The results of this study are the variables that affect employee performance are the reward variable, and the work environment. While the mutation variable does not affect the performance of employees at PT. Jasa Raharja Surabaya.